Using The 7 FE Framework in Business Process Management to Support Successful IT Project Management in Digital Banking - Yenny Israwati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
This research was conducted to see how the implementation of BPM at one bank in Indonesia using the 7 FE framework can help model the business process of digital management of banking products and services as a form of developing good processes. According to Becker, Breuker, Weiß, and Winkelmann (2010), the purpose of implementing BPM in banks is not only to reduce costs but also to reduce business process time and increase customer satisfaction by redesigning business processes so that they become more efficient. From the research results, it is known that the transformation of digital banking business process management using the 7 FE framework can provide convenience, speed and accuracy in managing the development of digital banking. Framework 7 FE. There are many BPM methodologies but the 7 FE framework provides an accurate and detailed approach to BPM implementation. This research is insightful that the implementation of BPM, especially by using the 7 FE framework, will assist banks in carrying out digital transformation. There are 10 phases in the framework called the 7FE Framework which is implemented throughout BPM, namely Foundation, Finding and Solution, Fulfillment, Future and Essentials